Characterization of self-organized crystalline Au nanoparticles embedded in epitaxially grown SrTiO3. Issue 7 (14th April 2015) - Bernhardt, Hendrik; Katzer, Christian; Undisz, Andreas; Drüe, Martin; Rettenmayr, Markus; Uschmann, Ingo; Schmidl, Frank
Abstract: Abstract : Crystalline Au nanoparticles embedded in epitaxially grown SrTiO3 layers were prepared by an annealing and coating procedure of Au seed layers on SrTiO3 (STO) substrates. X-ray diffraction and transmission electron microscopy measurements were performed to investigate the size, shape, and deformation of the particles and their crystal orientation. The shape and size of the crystalline Au nanoparticles can be tuned by controlling the Au seed layer thickness and single crystalline elliptically shaped Au nanoparticles have been generated. Furthermore, the orientation of the surrounding SrTiO3 matrix changes significantly from homoepitaxially grown (001) to secondary (111) and (011) orientations for Au seed layers that are thicker than 4 nm. This is of great interest for modifying the electrical properties of SrTiO3 layers, whereas the anisotropically shaped crystalline particles are relevant for optical applications, due to localized surface plasmon resonances.